Consultoría Y Asesoría Pedroza Celis S.A.S Empresa De Asesoría Contable, Tributaria, Y Revisoría Fiscal En La Ciudad De Santa Marta (2024)
The following project is based on creating an accounting, tax advisory and tax auditing company in the city of Santa Marta. This company will provide advisory services to small businesses to help them improve their financial management and comply with their tax obligations. Small businesses struggle to manage their finances effectively. This is because they usually have limited resources and staff with little experience in accounting and taxation. The consequences of this lack of financial management can be serious, such as not complying with tax and legal regulations, avoiding understanding financial statements and limiting the analysis that allows decision making. This project has the potential to contribute to the growth and development of small businesses in the region. The benefits of this project include: • Improvement of internal management of small businesses • More sustainable economic growth